Kinetic-Controlled Growth of Bi Nanostructures for Electrocatalytic CO2 Reduction. Issue 1 (29th January 2021) - Dong, Wan Jae; Hong, Dae Myung; Park, Jae Yong; Kim, Sungjoo; Yoo, Chul Jong; Lee, Jong-Lam
Abstract : Bi-based catalysts have attracted great attention for efficient electrocatalytic carbon dioxide (CO2 ) reduction to formic acid (HCOOH). However, the effect of the growth kinetics of Bi nanostructures on morphology and their catalytic performance has not been studied. Here, we varied the Bi 3+ precursor concentration in the electrolyte to control the electrochemical growth rate of Bi nanostructures. It was found that the growth rate determines not only the geometric structure but also the microstructure of Bi nanostructures. The slow growth with a low precursor concentration (1 mM) produced Bi nano-sheet (NS) with high crystallinity in (012) preferred orientation. But, the polycrystalline Bi nano-branch (NB) with a larger surface area was formed by a faster growth condition (precursor concentration = 30 mM). As a result, Bi NB achieved a higher FEHCOOH of 97.1% than Bi NS (FEHCOOH = 81.5%) at −1.0 VRHE . This work reveals that the growth condition of the Bi nanostructures plays a significant role in designing the catalysts for the efficient CO2 reduction reaction.